2017
DOI: 10.1097/md.0000000000006097
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the relationship between RASSF1A gene promoter methylation and bladder cancer (PRISMA)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In the case of hepatocellular carcinoma (HCC), the most common liver malignancy, hypermethylated RASSF1A was also detected in cancer tissue and serum samples of cancer patients. In contrast, it was not detected in healthy controls (63,64).…”
Section: Gastrointestinal Cancermentioning
confidence: 73%
See 2 more Smart Citations
“…In the case of hepatocellular carcinoma (HCC), the most common liver malignancy, hypermethylated RASSF1A was also detected in cancer tissue and serum samples of cancer patients. In contrast, it was not detected in healthy controls (63,64).…”
Section: Gastrointestinal Cancermentioning
confidence: 73%
“…Combined methylation analysis of two genes, HOXA9/RASSF1A had successfully distinguished two subgroups, nonseminomas, and seminomas in TGCT diagnostics (88,89). In BCA, significantly higher methylation was detected in muscle-invasive BCA than non-invasive one (64,81).…”
Section: Methylation Of Rassf1a In Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Its increased expression can mainly make tumor cells resistant to cisplatin (24). The aberrant methylation of RASSF1A gene serves an important role in the occurrence and development of various tumors, including bladder cancer and thyroid cancer (25,26), and is associated with drug resistance and tumor prognosis (27,28). The purpose of the present study was to detect the expression of drug resistance genes and aberrant methylation of RASSF1A in different types of ovarian tissues and to investigate their role in the primary resistance of ovarian cancer.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the methylation degree of miR-608 was higher in two cancer cells lines compared with normal cell line with the methylation level of 91.4% and 87.3% respectively, and also proposed that CpG islands hypermethylation might cause the silencing of mRNA expression [18]. In addition, Zhou et al implicated that DBCCR1 down regulation acted as an underlying module via DNA methylation in the lung cancer pathogenesis [19]. However, it was reported that the neural transcription factors ZIC1 and ZIC4 were up regulated in desmoid tumors and other broproliferative disorder diseases, the promoter performed unmethylated in tumor tissues compared to normal tissues [20].…”
Section: Discussionmentioning
confidence: 99%